Methods for quantifying training in sprint kayak - Borges, T. O.; Bullock, N.; Duff, C.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2014)
The aims of this study were to determine the validity of the session rating of perceived exertion (session-RPE) method by comparing 3 different scales of perceived exertion with common measures of training load (TL). A secondary aim was to verify the relationship between TLs, fitness, and performance in Sprint Kayak athletes. After laboratory assessment of maximal oxygen uptake (VO2peak) and lactate threshold, the athletes performed on water time trials over 200 and 1,000 m. Training load was quantified for external (distance and speed) and internal (session-RPE: 6-20, category ratio [CR]-10 and CR-100 scales, training impulse [TRIMP], and individual TRIMP). Ten (6 male, 4 female) well-trained junior Sprint Kayak athletes (age 17.1 ± 1.2 years; VO2peak 4.2 ± 0.7 L/min) were monitored over a 7-week period. There were large-to-very large within-individual correlations between the session distance and the various heart rate (HR) and RPE-based methods for quantifying TL (0.58-0.91). Correlations between the mean session speed and various HR- and RPE-based methods for quantifying TL were small to large (0.12-0.50). The within-individual relationships between the various objective and subjective methods of internal TL were large to very large (0.62-0.94). Moderate-to-large inverse relationships were found between mean session-RPE TL and various aerobic fitness variables (-0.58 to -0.37). Large-to-very large relationships were found between mean session-RPE TL and on water performance (0.57-0.75). In conclusion, session-RPE is a valid method for monitoring TL for junior Sprint Kayak athletes, regardless of the RPE scale used. The session-RPE TL relates to fitness and performance, supporting the use of session-RPE in Sprint Kayak training.